2020
DOI: 10.1080/20008686.2020.1764693
|View full text |Cite
|
Sign up to set email alerts
|

Spatial tick bite exposure and associated risk factors in Scandinavia

Abstract: Tick-borne diseases are emerging and re-emerging threats causing public health concerns in Europe and North America. Prevention and control requires understanding of human exposure and behaviour. The aim was to measure exposure to tick bites across Scandinavia, its spatial distribution and the associated risk factors. Methods We sent a web-based survey to a randomly chosen population and analysed answers by Principal Component Analysis and Chi-Square. Individual responses were aggregated at the municipality le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Many unrecorded factors can influence human exposure to ticks, but owning a furred animal does not seem to be an isolated risk factor. A Scandinavian study on risk factors neither found an association between pet ownership and reported tick bites, but between outdoor activities and reported tick bites [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many unrecorded factors can influence human exposure to ticks, but owning a furred animal does not seem to be an isolated risk factor. A Scandinavian study on risk factors neither found an association between pet ownership and reported tick bites, but between outdoor activities and reported tick bites [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ticks occur less in pine forest and least in grass and heath, explained by ticks being exposed to more desiccating weather conditions in open vegetation [ 27 , 29 ]. Several studies have linked the presence of ticks with the incidence of pathogens in ticks, humans, and animals [ 11 , 30 , 31 , 32 ]. In general, the findings confirm that not all, but varying percentages of ticks are carriers of the pathogens, sometimes more in females and in nymph stages.…”
Section: Climate-sensitive Infections: the Tickmentioning
confidence: 99%
“…Several Nordic studies on ticks and TBDs have shown that I. ricinus has changed its distribution in recent decennia [ 20 , 45 , 57 , 58 ], with a northward migration of approximately 400 km within the past 20–30 years in Norway [ 58 , 59 ], up to 150–250 km north of the Arctic Circle, though with a sparser presence north of 65° N [ 60 , 61 ]. A recent study by Hvidsten et al [ 45 ] found that the northernmost permanent I. ricinus population was located at 66.22° N at the coast, although this study did not have national coverage and used only one method (flagging) with low efficiency, and cannot therefore be used to verify presence or absence [ 32 ]. Nevertheless, the study suggests presence at a high latitude, and the range expansion indicated in the area of 69° N (northern tip of Sweden) is in line with the distributional limit predicted previously [ 20 , 28 , 31 ].…”
Section: What Does a Changing Climate Mean For Ticks And Csis?mentioning
confidence: 99%
See 1 more Smart Citation
“…The expected proportion of orienteers bitten by ticks is therefore between 33% and 62% during the six days of the competition and between 10% to 42% per day, which is in either case very high. For comparison with general populations of other countries, a range of 45–60% of respondents reported finding attached ticks over a preceding 12-month period in surveys conducted in Scandinavia [ 47 ] and in North-West Italy [ 48 ]. In endemic areas of Lyme disease in USA, this proportion was in the range of 10–37% [ 25 ], and in France it has been estimated that only 4.1% of the general population was bitten over a period of 12 months [ 46 ].…”
Section: Discussionmentioning
confidence: 99%